ION-IMPRINTED POLYMER WITH MAGNETITE CORE FOR SEPARATION AND PRECONCENTRATION IN CD(II) ION ANALYSIS - Halim, Albert
In this industry era, there are so many industry that produce various kinds of waste such as paint industry, electrical tools, and metal coating. Cadmium as a heavy metal is a waste that endanger to plants, animals, and also humans because it is hard to be degraded in body. Cadmium can be determined using separation and preconcentration methods. Several methods that have been done is liquid-liquid extraction, solid-liquid extraction, ion exchange. Recently it became known that, sorbent that based on ion imprinted polymer has higher selectivity and affinity for metal ion target. The usage of IIP with magnetite core will have large surface area so, extraction process will be quick. In this research, the synthesis of magnetite core is using coprecipitation method with mole ratio of FeSO4.7H2O : FeCl3.6H2O is 1 : 2 dan with addition of NH3 25% then, magnetite core is coated with SiO2 using TEOS (tetraethyl orthosilicate). The process of synthesis NIP (Non Imprinted Polymer) used magnetite encapsulated silicate and MPTS (3-Mercaptopropyl) trimethoxysilane. The results of characterization using Fourier Transform Infrared (FTIR) showed absorption at wavenumber 578 cm-1 for Fe-O bonds and for Fe3O4@SiO2 showed absorption at wavenumber 1098 cm-1 for O-Si-O and 562 cm-1 for Fe-O. For NIP the wavenumber is 2551 cm-1 for S-H and IIP showed wavenumber 2553 cm-1 for S-H. the result of Scanning Electron Microscope-Energy Dispersive Spectroscopy (SEM- EDS) showed that magnetite have a composition of 64,35% Fe and 35,65% O. Fe3O4@SiO2 have a composition of 66,61% O, 29,72% Fe, and 3,67% Si.